Ultrahigh Speed and Broadband Few‐Layer MoTe2/Si 2D–3D Heterojunction‐Based Photodiodes Fabricated by Pulsed Laser Deposition. (7th January 2020) - Lu, Zhijian; Xu, Yan; Yu, Yongqiang; Xu, Kewei; Mao, Jie; Xu, Gaobin; Ma, Yuanming; Wu, Di; Jie, Jiansheng
Abstract: 2D transition metal dichalcogenides are promising candidates for high‐performance photodetectors. However, the relatively low response speed as well as the complex transfer process hinders their wide applications. Herein, for the first time, the fabrication of a few‐layer MoTe2 /Si 2D–3D vertical heterojunction for high‐speed and broadband photodiodes by a pulsed laser deposition technique is reported. Owing to the high junction quality, ultrathin MoTe2 film thickness, and unique vertical n–n heterojunction structure, the photodiode exhibits excellent device performance in terms of a high responsivity of 0.19 A W −1 and a large detectivity of 6.8 × 10 13 Jones. The device is also capable of detecting a broadband light with wavelength spanning from 300 to 1800 nm. More importantly, the device possesses an ultrahigh response speed up to 150 ns with a 3‐dB electrical bandwidth approaching 0.12 GHz. This work paves the way toward the fabrication of novel 2D–3D heterojunctions for high‐performance, ultrafast photodetectors. Abstract : A few‐layer MoTe2 /Si 2D–3D photodiode is constructed by a pulsed laser deposition method. Owing to the high junction quality, ultrathin MoTe2 film thickness, and unique vertical n–n heterojunction structure, the device exhibits a broadband spectral response from 300 to 1800 nm, an ultrahigh response speed of 150 ns, and a large 3‐dB electrical bandwidth up to 0.12 GHz.